2005
DOI: 10.1159/000086827
|View full text |Cite
|
Sign up to set email alerts
|

Arnold-Chiari in a Fetal Rat Model of Dysraphism

Abstract: Dysraphism is a defect in neural tube development, leading to dysplastic growth of the spinal cord and meninges. Myelomeningocele (MM) is just one of its forms. Hydrocephalus is among the most important alterations in MM and occurs as a consequence of Arnold-Chiari malformation (AC). Experimental models have been developed in sheep, rabbits and rats to study MM physiopathology, allowing a more detailed evaluation of clinical parameters involved in this anomaly. Objective: Using the experimental model of dysrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…In 1996, we reported Chiari-like malformation associated with surgically induced ONTD in chick embryos at midgestation (total age, 14 days) [ 12 ]. Other surgical experimental models of CM II associated with spinal ONTD were demonstrated in mice by Inagaki et al [ 7 ], in rats by Weber Guimarães Barreto et al [ 14 ] and in lambs by Fontecha et al [ 3 ]. In 2000, Paek et al [ 9 ] reported the first large animal model using sheep to demonstrate hindbrain herniation associated with myelomeningocele.…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, we reported Chiari-like malformation associated with surgically induced ONTD in chick embryos at midgestation (total age, 14 days) [ 12 ]. Other surgical experimental models of CM II associated with spinal ONTD were demonstrated in mice by Inagaki et al [ 7 ], in rats by Weber Guimarães Barreto et al [ 14 ] and in lambs by Fontecha et al [ 3 ]. In 2000, Paek et al [ 9 ] reported the first large animal model using sheep to demonstrate hindbrain herniation associated with myelomeningocele.…”
Section: Introductionmentioning
confidence: 99%
“…Após análise dos modelos experimentais que foram desenvolvidos em ovelhas, coelhos e ratos para estudar a fisiopatologia da mielomeningocele, permitindo uma avaliação mais detalhada de parâmetros clínicos envolvendo esta anomalia. Weber GuimarãesBarreto et al (2005) do Grupo de Medicina Fetal -UNICAMP, decidiram usar o modelo experimental de disrafismo em ratos fetais, com o objetivo de avaliar a relevância de malformações de Arnold-Chiari, em relação aos parâmetros clínicos e grau de lesões histológicas. Três grupos com 16 fetos em cada foram comparados, ratos com mielomeningocele, ratos controle e ratos fraude, depois da criação cirúrgica da mielomeningocele intra-útero no dia 18,5 de gestação (termo = 22 dias).…”
unclassified